On the understanding of the microscopic origin of the properties of diluted magnetic semiconductors by atom probe tomography - Zheng, R; Moody, M; Gault, B; Liu, Z; Liu, H; Ringer, S (2009)
Spintronics, in which both the spin and charge of electrons are used for logic and memory operations, promises to revolutionize the current information technology. Just as silicon supports microelectronics, diluted magnetic semiconductors (DMSs) will be the platform of spintronics. Ideal DMSs should maintain ferromagnetic and semiconducting properties at operating temperatures to realize the spintronic functions. Although many high-temperature Curie temperature DMSs have been reported, the origin of ferromagnetism remains controversial. Currently, this is a major obstacle to the development of spintronic devices. The solution to this problem depends on a more complete understanding of DMS microstructure, especially the distribution of doped magnetic ions at atomic resolution and any defects introduced. Therefore, an analysis technique is required, possessing both high spatial and elemental resolutions, which is beyond the capability of conventional techniques, such as electron microscopy. However, atom probe tomography (APT), which recently has been successfully applied to nanoscale characterization of structural materials, has the potential to provide the unique combination of near atomic spatial and elemental resolutions needed for such an investigation. © 2008 Elsevier B.V. All rights reserved.